Struktur Komunitas Lichenes di Kawasan Gunung Galunggung Berdasarkan Indeks Ekologi - Nuralamsyah, Muhamad; Hernawati, Diana; Putra, Rinaldi Rizal (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Lichenes are a symbiosis between fungi and algae which usually grow on rock surfaces, rotting logs, and trees. This research is to determine the community structure of Lichenes in the Mount Galunggung Region based on ecological indexes. The research method was carried out in a descriptive exploratory survey technique, where the area taken from each station was 300 m. The areas that are the research stations are the Crater Area, Batu Blek Waterfall, and Cipanas Waterfall. The number of Lichenes found consisted of 4 classes, 9 orders, 13 families, 16 genera and 17 species of Lichenes, including station 1 (Crater Area) there were 10 species with the highest number of individuals found in the species Graphis sp. namely 669 individuals (63%). Station 2 (Curug Batu Blek) there are 6 species with the highest number of individuals found in the species Graphis sp. namely 412 individuals (59%). Station 3 (Curug Cipanas) there were 6 species with the highest number of individuals found in the species Cryptothecia striata, amounting to 637 individuals (34%). The average value of the diversity index was 1.20 which included the medium category, the evenness index value was 0.62 which included the high category, the species richness index value was 0.91 which included the low category, the species dominance index value was 0.39 which included the medium category. The environmental parameters include chemical factors (pH) and physical factors (temperature, light intensity, humidity, type of substrate, and altitude).